Correction to: Inter-provincial inequality of public health services in China: the perspective of local officials' behavior - Tianxiang Chen; Ying Wang; Xiaoyi Luo; Yuxuan Rao; Lei Hua (BMC, 2018)
Unfortunately, after publication of this article [1], it was noticed that a value in Table 2 is incorrect.